Work and depression: The moderating role of personality traits. (3rd July 2019) - Parent-Lamarche, Annick; Marchand, Alain
Abstract: Background: Some stress theories argue that the effects of stressors are moderated by the individual perception of stressors. Personality traits may thus moderate the relationship between work stressors and depression. Objective and method: This study aims to verify the moderating effect of personality traits on the relationship between work conditions and depression. Multilevel regression analyzes were performed on a sample of 1957 workers employed in 63 Quebec firms. Work variables included skill utilization, decision authority, psychological demands, physical demands, job insecurity, irregular schedule, number of working hours, social support from colleagues and supervisors, and personality traits included self-esteem, locus of control, Big Five. Results and conclusion: Certain specific personality traits (self-esteem, locus of control) and general personality traits (openness, extraversion, and conscientiousness) play a moderating role on the relationship between working conditions (skill utilization, physical demands, support from colleagues, job insecurity) and depression. The results of this study may be useful in some human resource management activities, particularly career management, promotions management, and personnel selection. Additional research will, however, be necessary to gain a more complete understanding of the full range of determinants affecting depression.